Regional Differences in the Accumulation of SNPs on the Male-Specific Portion of the Human Y Chromosome Replicate Autosomal Patterns: Implications for Genetic Dating - Trombetta, Beniamino (PLoS One, 2015)
Factors affecting the rate and pattern of the mutational process are being identified for human autosomes, but the same relationships for the male specific portion of the Y chromosome (MSY) are not established. We considered 3,390 mutations occurring in 19 sequence bins identified by sequencing 1.5 Mb of the MSY from each of 104 present-day chromosomes. The occurrence of mutations was not proportional to the amount of sequenced bases in each bin, with a 2-fold variation. The regression of the number of mutations per unit sequence against a number of indicators of the genomic features of each bin, revealed the same fundamental patterns as in the autosomes. By considering the sequences of the same region from two precisely dated ancient specimens, we obtained a calibrated region-specific substitution rate of 0.716 × 10(-9)/site/year. Despite its lack of recombination and other peculiar features, the MSY then resembles the autosomes in displaying a marked regional heterogeneity of the mutation rate. An immediate implication is that a given figure for the substitution rate only makes sense if bound to a specific DNA region. By strictly applying this principle we obtained an unbiased estimate of the antiquity of lineages relevant to the genetic history of the human Y chromosome. In particular, the two deepest nodes of the tree highlight the survival, in Central-Western Africa, of lineages whose coalescence (291 ky, 95% C.I. 253–343) predates the emergence of anatomically modern features in the fossil record.